Method of stakeholders' identification based on their views in strategic management of social programs - Kadykova, Iryna; Ovsiuchenko, Yurii; Chumachenkо, Igor (Національний технічний університет "Харківський політехнічний інститут", 2022)
There has been proposed the method of stakeholders' identification in strategic management of social programs. It is designed to recognize and assess the strength of causal relationships of failure of social projects and programs. The method is based on the differentiation of stakeholders by their ideas, which is revealed in the example of inclusive educational projects. The concept of stakeholder priority number has been introduced. The matrix "risk priority number" / "stakeholder priority number" is offered. We have developed the method of stakeholders’ identification based on their views in the strategic management of social programs, which consists of 7 Steps. Step 1: development of a questionnaire for the cause-and-effect relationships of the failure of inclusive educational projects according to the imagination of stakeholders of different groups. Step 2: survey of respondents with differentiation by stakeholder priority number and three groups of stakeholders: the state as a system of institutions; citizens with disabilities or their legal representatives; neurotypical visitors to institutions or their legal representatives. Step 3: investigation of stakeholders' perceptions of the cause-and-effect relationships of failure of inclusive projects according to the 6M method (Lan, Machines, Materials, Methods, Measurements, Mother-nature). Step 4: charting of Isikawa diagrams.

Пропонується метод ідентифікації стейкхолдерів у стратегічному управлінні соціальними програмами, призначений для виявлення та оцінювання потужності причинно-наслідкових зв’язків неуспішності соціальних проєктів та програм. Метод ґрунтується на диференціації різних груп стейкхолдерів за їх уявленнями, що розкривається на прикладі інклюзивних освітніх проєктів. Введене поняття пріоритетного числа стейкхолдера. Запропонована матриця «пріоритетне число ризику» / «пріоритетне число стейкхолдера». Розроблений метод ідентифікації стейкхолдерів на основі їх уявлень у стратегічному управлінні соціальними програмами, який складається з 7 етапів. Етап 1: розробка анкети щодо причинно-наслідкових зв’язків неуспішності інклюзивних освітніх проєктів за уявою стейкхолдерів різних груп. Етап 2: опитування респондентів з диференціацією за пріоритетним числом стейкхолдера та трьома групами стейкхолдерів: держава як система інституцій; громадяни з інвалідністю або їх законні представники; нейротипові відвідувачі закладів/установ або їх законні представники. Етап 3: дослідження уявлень стейкхолдерів про причинно-наслідкові зв’язки неуспішності інклюзивних проєктів за методом 6М (Man, Machines, Materials, Methods, Measurements, Mother-nature). Етап 4: побудова діаграм Ісікави.
Метод идентификации стейкхолдеров на основе их представлений в стратегическом управлении социальными программами
Keywords: socio-economic reforms; program management; inclusion; stakeholder; strategic management; social programs; project management; соціально-економічні реформи; стейкхолдер; стратегічне управління; соціальні програми; проєктний менеджмент; програмне управління